(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
The 2013 curriculum emphasizes on active student learning with a scientific approach and authentic assessment. This paper aims to explicate the teachers’ complexity in implementing the scientific approach and authentic assessment in English language teaching process. The 2013 curriculum introduces and encourages the use of scientific approach in the learning process for all subjects including English. Scientific approach is an approach that focuses on finding facts, concepts, principles, laws and theories. By this approach, it is hoped that the students’ learning outcomes can be more attached as they do it with fact based procedure. Withal, authentic assessment is also emphasized in the 2013 curriculum, where this assessment not only focus on the final result but also on the learning process. This paper focuses on : the implementation of scientific approach and authentic assessment in English language teaching process, and the barriers faced by teachers in implementing scientific approach and authentic assessment. Qualitative descriptive was applied in this study. To obtain the data needed, interview was used as instrument in this study. There were several conclusions obtained from the results of this study; 1) The implementation of scientific approach was in accordance with approach. In terms of assessment, the English teacher has implemented the authentic assessment, that is a measurement of students’ learning outcome in three domains (cognitive assessment, affective assessment an skill). But in its implementation, this has also not been implemented in a manner maximum. 2) The barrier faced the principles or rules. In lesson plan, the teachers clearly described the steps of scientific approach with using variety of methods or techniques in teaching English, even though on the process of teaching and learning English in the class, the teacher rarely used this by the teacher in applying scientific approach was to facilitate the students in asking and answer questions among them, while in authentic assessment, the obstacles were limited time, limited facilities and infrastructure, difficulty in implementing certain models of authentic assessment, and students.